"A sense of wider fields and chances": Towards a literary history of English-Canadian satiric fictions of the nineteenth century. - Robbeson, Angela. (University of Ottawa (Canada), 1998)
This dissertation combines literary analysis with genre study and cultural history to trace the evolution of a tradition of nineteenth-century Canadian satiric fiction. Through a close reading of canonical texts examined within the contexts of their production, I analyze the moral, social, and political norms that inform nineteenth-century Canadian satire and determine how these norms have either been maintained or modified. The introduction defines the key terms of the thesis by reviewing the principle theoretical arguments surrounding the study of satire, and by elaborating the critical stance as one informed by the reading practices of New Criticism and Historicism. Part One explores the development of the satiric sketch in the Colonial Period and focuses on Thomas McCulloch's The Stepsure Letters (1821--3) and Thomas Chandler Haliburton's The Clockmaker (first series, 1836). In their condemnation of the vices and follies exhibited by their neighbours, McCulloch and Haliburton share many of the same norms; however, the evolution of the satiric viewpoint is one of ever-broadening scope. Both writers focus on similar class and social issues, for instance, but Haliburton also considers larger political matters centred around the complicated issue of Imperialism. Part Two examines the rise of the satiric novel in the Confederation Period and focuses on James De Mille's A Strange Manuscript Found in a Copper Cylinder (1888) and Sara Jeannette Duncan's The Imperialist (1904), which both take up the "Imperial Question." De Mille's fantastical adventure questions both Christian doctrine and Victorian values in its profound exploration of the individual challenge to define a code of values by which to live, and its thoughtful inquiry into the imperialistic urge to impose those values on others. Duncan's authentic depiction of turn-of-the-century small town Ontario's emotional and intellectual responses to the political debate on international relations satirizes the ignorant assumptions and lack of imagination displayed by both Canadians and Britons. The conclusion surveys the ways in which these writers urge their readers to recognize the "wider fields and chances" available to them; that is, the geographical, philosophical, and imaginative spaces open to all colonists/Canadians, and the attendant social, economic, and spiritual opportunities, risks, and responsibilities to be encountered there.
Keywords: Literature, Canadian (English).